Conflicting HLA assignment by three different typing methods due to the apparent loss of heterozygosity in the MHC region. (10th March 2016) - Linjama, T.; Impola, U.; Niittyvuopio, R.; Kuittinen, O.; Kaare, A.; Rimpiläinen, J.; Volin, L.; Peräsaari, J.; Jaatinen, T.; Lauronen, J.; Saarinen, T.; Juvonen, E.; et al.
Abstract: Loss of heterozygosity (LOH) has been reported to cause false human leukocyte antigen (HLA) homozygous typing results in pre‐transplant patients suffering from haematological malignancies, who in fact are HLA heterozygous. This poses a challenge for histocompatibility testing, as a stem cell graft from a genuinely HLA homozygous donor to a mistyped patient may lead to acute life‐threatening graft‐ vs ‐host disease. LOH in the HLA region on chromosome 6 is known to be quite common in solid tumours, helping malignant cells to escape T‐cell surveillance, but the incidence in haematological malignancies is less well known and the estimates vary. Here we report LOH in the HLA region of five patients with haematological malignancy. We found considerable differences in sensitivity between the three different HLA typing methods used in our laboratory: SSP was clearly the most sensitive method for detecting the lost haplotype, followed by rSSO, while SBT was the least sensitive technique. A subsequent, retrospective genotyping of 65 HLA homozygous haematological patients by SSP method showed no mistyped LOH cases in our laboratory in the past 10 years. The frequency of HLA homozygosity was found to be similar between haematological patients and control groups. It is important for an HLA laboratory to be aware of the differences in various HLA typing techniques' sensitivity for detecting an under‐represented haplotype between HLA typing techniques when genotyping patients with haematological diseases. It is advisable for HLA laboratories to have at least two different methods with different sensitivities in their repertoire to be able to retype samples when a false homozygous result is suspected.